The diva delivers on a promise - Davis, Krista (Davis, Krista. Domestic diva mystery., 2023)
"Sophie is busy handling the first ever convention of the Association of Ghost Kitchens--restaurants that do delivery only--but she's taking a little time out for a lunch meeting organized by A Healthy Meal. The group is dedicated to providing meals for children in need, and as a bonus, it'll give Sophie the perfect opportunity to ogle the lavish Old Town home of socialite Geraldine Stansfield. Gerrie's dining room is impeccably furnished, the table laden with gleaming crystal and prized china. If it weren't for the dead man lying on the floor, everything would be perfect ..."--